Comparative Analysis Of Gold Price Volatility And Risk-Return Relationship Against Eight Metal Commodities. - Ujang, Noridah (2003)
This research will look at the core of the 'Gold Dinar', that is the gold itself. The research showed that gold is preferred compared with any other metals and gold is viable to become the currency for Bilateral Payment Arrangement and Multilateral Payment Arrangement. The lower volatility of gold price shall make it very difficult to be speculated.